1982
DOI: 10.1161/01.atv.2.3.266
|View full text |Cite
|
Sign up to set email alerts
|

Systemic arterial compliance in patients with arteriosclerosis obliterans of the lower limbs. Observations on the effect of intravenous propranolol.

Abstract: Hemodynamic parameters and systemic arterial compliance were measured in patients with arteriosclerosis obliterans of the lower limbs before and after acute administration of propranolol. Arterial compliance was evaluated from a simple viscoelastic model, enabling the calculation of diastoiic drainage and diastoiic blood flow as indices of the reservoir role of the large arteries in overall circulation, in comparing basal conditions with normal subjects of the same age, patients with arteriosclerosis obliteran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0

Year Published

1984
1984
2008
2008

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…Indeed, it has been shown in patients with arteriosclerosis obliterans that decreased arterial compliance is exaggerated by beta-blockade. 1 Within the limits of the present investigation, it is difficult to assess the basis for an alteration in the autonomic system of patients with arteriosclerosis obliterans. One of the more surprising findings of this study was the observation of a slight, but significant, decrease in heart rate, as already reported.…”
mentioning
confidence: 78%
“…Indeed, it has been shown in patients with arteriosclerosis obliterans that decreased arterial compliance is exaggerated by beta-blockade. 1 Within the limits of the present investigation, it is difficult to assess the basis for an alteration in the autonomic system of patients with arteriosclerosis obliterans. One of the more surprising findings of this study was the observation of a slight, but significant, decrease in heart rate, as already reported.…”
mentioning
confidence: 78%
“…18 Increased SBP in PAD seems to be due to a combination of arterial stiffness and reflection sites being closer to the heart, resulting in an increase in the rate and amplitude of central wave reflection. 19,20 The finding of ISH in the PAD cohort in the ATTEST study may also be a reflection of the increased age associated with onset of this condition. With age, increased arterial stiffness leads to increased SBP with a decrease in DBP, resulting in a higher pulse pressure.…”
mentioning
confidence: 99%
“…Sodium excess and b-blocking agents may increase SBP through increase in arterial stiffness and disturbed wave reflections, whereas nitrates and angiotensin-converting enzyme inhibitors (ACEI) have an opposite effect. 12,[16][17][18] Third, stenoses of renal artery are relatively frequent in subjects with PAD and favour the presence of systolic-diastolic hypertension. 19 Finally, clinical studies have shown that increased arterial stiffness and disturbed wave reflections are not only frequent in subjects with PAD but also are significantly associated with reduced walking distance and impaired vasodilating arteriolar properties.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Increased SBP in subjects with PAD is mainly because of increased arterial stiffness and disturbed timing and amplitude of central wave reflections. [12][13][14] More specifically, reflection sites are closer from the heart than in normal subjects, because of the importance of structural alterations of the aortic bifurcations, as extensively shown from arteriography. 12 This interpretation is strengthened by the presence of an increased frequency of systolic hypertension around 50 years of age in subjects with traumatic amputation of the lower limbs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation